Aging in Sub-Saharan Africa: Recommendations for Furthering Research - National Research Council (U.S.). Panel on Policy and Data Needs to Meet the Challenge of Aging in Africa; Cohen, Barney; Menken, Jane A. (National Academies Press, 2006)
In sub-Saharan Africa, older people make up a relatively small fraction of the total population and are supported primarily by family and other kinship networks. They have traditionally been viewed as repositories of information and wisdom, and are critical pillars of the community but as the HIV/AIDS pandemic destroys family systems, the elderly increasingly have to deal with the loss of their own support while absorbing the additional responsibilities of caring for their orphaned grandchildren. Aging in Sub-Saharan Africa explores ways to promote U.S. research interests and to augment the sub-Saharan governments' capacity to address the many challenges posed by population aging. Five major themes are explored in the book such as the need for a basic definition of "older person," the need for national governments to invest more in basic research and the coordination of data collection across countries, and the need for improved dialogue between local researchers and policy makers. This book makes three major recommendations: 1) the development of a research agenda 2) enhancing research opportunity and implementation and 3) the translation of research findings.